Răspunsuri

2014-07-22T23:05:04+03:00
2a) √147=7√3
√75=5√3
√243=9√3
√27=3√3

7√3 +5√3 -9√3 +3√3= 15√3-9√3= 6√3

b) 2√32= 2* 4√2=8√2
√72=6√2
√162= 9√2
3√242= 3*11√2= 33√2

a= √2( 8√2 - 6√2 +9√2 -33√2)= 8*2 -6*2 +9*2 -33*2=  16 -12 +18 -66=  34- 78= -44

c) 5⁻²= 1/5²=  1/25

√42,25=6,5=6 intregi 5/10= 6 intregi 1/2= 13/2
7,(9)=7 intregi 9/9= 72/9=8
(1/√5 -5√5)=  (√5/5 -5√5)=  (√5-25√5)/5=  -24√5/5

1/25 :1/100 + 13/2 *8 + √5 * -24√5/5= 1/25 * 100/1 + 13*4 + -24*5/5=

=4+ 52 -24= 56 -24= 32

3a) | 4√5-9|=  -4√5+9= -4* 2,23+9= -8,94+9= 0,06

|√19-3√2|= √19-3√2= 4,35 - 3*1,41= 4,35 -4,23= 0,13

b)2√108=2 *6√3=12√3

|3√3-2| +12√3=  3√3-2+12√3= 15√3 -2

c) ( |4√3 -7| * (4√3+7) )²⁰⁰⁶=  (48-49)²⁰⁰⁶=  (-1)²⁰⁰⁶= 1

4a)(√5+3)²= 5+6√5+9= 14+6√5

(4-√15)²=16-8√15+15=  21-8√15

b)(5+2√15+3) * (8-2√15)=  (8+2√15)(8-2√15)= 64- 60=4

c)a=(7-5√2)(7+5√2)= 49- 50=-1

b= |2-√3| - |3-√3|= 2-√3 -3+√3= 2-3=-1

a=b=-1

5)a) x/2√10= x√10/20

3√8/√5= 3√40/5= 3*2√10/5=  6√10/5

√32/5= 4√2/5

x√10/20 -6√10/5= 4√2/5   aducem la acelasi numitor

x√10-24√10=16√2

x√10=16√2+24√10

x=(16√2+24√10)/√10=  (16*2√5+24*10)/10= 2(16√5+24*5)/10=  (16√5+120)/5

b)A n B= [1;√10]

A u B= [-1;5]

A - B= (√10;5]

B - A= [-1;1)

c) (6+5√6)/√3= (6√3+5*3√2)/3=  3(2√3+5√2)/3=  2√3+5√2

(4+2√6)/√2= (4√2+ 2*2√3)/2= 2(2√2+2√3)/2= 2√2+2√3

(3-2√6)/√3= (3√3-2*3√2)/3= 3(√3-2√2)/3= √3-2√2

(8-√6)/√2= (8√2-2√3)/2= 2(4√2-√3)/2= 4√2-√3

(2√3+5√2-2√2-2√3+√3-2√2 -4√2+√3) * (2√3 +3√2)=

=(√3+√3 +5√2 -8√2) * (2√3+3√2)= (2√3-3√2)*(2√3+3√2)= 12- 18= -6

6a) (2x+1)/3 + (6x-1)/5= (23x-8)/15  aducem la acelasi numitor

5(2x+1)+3(6x-1)=23x-8

10x+5+18x-3=23x-8

28x+2=23x-8

28x-23x=-8-2

5x=-10
x=-2

b) 0,3( 10x-60) -0,5(8x+4) ≥ x-25

3x-18 -4x -2 ≥ x-25

-x -20 ≥ x-25

-x-x ≥ -25+20

-2x ≥ -5 |-1

2x ≤ 5

x ≤ 5/2   ⇒x∈ (-α;5/2]



1 5 1